Response of Prospective Mathematics Teacher Students To Learning Difficulties In Calculus Course - Vrasetya, Arshinta; Nasution, Eline Yanty Putri; Handican, Rhomiy (Universitas Wiralodra, 2024)
This study was motivated by the learning difficulties faced by prospective mathematics teacher students in calculus courses, while calculus courses studied at the college level equip prospective teacher students to teach mathematics subjects at the secondary school level. This study aims to determine students' responses to learning difficulties in calculus courses. This research used descriptive quantitative method by involving 25 students of Tadris Mathematics IAIN Kerinci as the research sample. The sampling technique used in this study was convenience sampling, which is when a researcher chooses his sample only by including people who are available. This study uses a closed questionnaire as a data collection tool that is reviewed from 7 aspects of difficulty, namely interest, motivation, talent, intelligence, facilities and infrastructure, quality, and teaching methods. The results of descriptive analysis showed that students have a high level of difficulty in learning calculus. The conclusion of this study shows that students' learning difficulties, especially in calculus courses, are strongly influenced by external factors, especially related to learning facilities and infrastructure. The results also show that prospective math teacher students at IAIN Kerinci have an unfavorable response to learning difficulties in calculus courses.